Impact of Arctic sea ice on the boreal summer intraseasonal oscillation - Zihuang Xie; Yao Ha; Yimin Zhu; Yijia Hu; Zhong Zhong (Climate Dynamics, 2024)
This study investigates the relationship between sea ice concentration (SIC) in the Arctic Ocean and the Boreal Summer Intraseasonal Oscillation (BSISO) from 1991 to 2020 and its underlying mechanism. A significantly positive (negative) correlation was found between the frequency of phase 7 (3) of BSISO1 (30–60 d) and the preceding winter SIC, which is located the north of the East Siberian-Beaufort Sea (ESBS). Compared with low-SIC years, the conditions including northeasterly vertical wind shear, an enhanced ascending branch of the anomalous Walker circulation, an eastward water vapour transport channel, and an increased humidity gradient induce active convection over the Philippine Sea in high-SIC years, which benefits (hinders) to phase 7 (3) of BSISO1. The positive SIC anomaly during the transition from winter to spring influences local temperature and pressure through anomalous local sensible heat flux. This anomaly induces wave activity flux from the ESBS, which converges over the Bering Sea, enhancing the Aleutian Low (AL). Subsequently, the AL triggers an anomalous subtropical anticyclone through wave-mean flow interaction in the North Pacific. Due to southerly wind stress and increased sea surface heat flux, positive sea surface temperature anomalies near Japan persist in the summer, heating the lower troposphere and increasing baroclinicity. Significant positive geopotential heights and anticyclone anomalies occur over Japan, accompanied by a negative vorticity anomaly. The enhanced ascending motion over the Philippine Sea, facilitated by Ekman pumping, favours convection and influences the frequency of phases 7 and 3.